ANALISIS KINERJA ASN DI WILAYAH KERJA DINAS KESEHATAN PROVINSI SUMATERA SELATAN - Lisdiana, Lisdiana; Hestiriniah, Deby Chintia; Muliawati, Imelda; Novaria, Eva (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The purpose of this study is to analyze the Performance of ASN in the Work Area of ??the South Sumatra Provincial Health Office. This study uses a qualitative approach supported by quantitative data. In this study, the researcher intends to obtain an in-depth and comprehensive picture of the analysis of ASN performance in the work area of ??the South Sumatra Provincial Health Office. The approach used in this study is a qualitative approach. The conclusions of the study are: 1). The performance of ASN in the work area of ??the South Sumatra Provincial Health Office is categorized as good. The performance of State Civil Apparatus (ASN) in the work area of ??the South Sumatra Provincial Health Office includes various aspects such as ability and expertise, knowledge, work design, personality, work motivation, leadership, leadership style, organizational culture, job satisfaction including the work environment, and the performance report of government agencies of the South Sumatra Provincial Health Office can provide a more detailed picture of ASN performance in various fields, including achievements, challenges, and efforts made to improve the performance of employees of the South Sumatra Provincial Health Office. 2). Problems in ASN Performance in the South Sumatra Provincial Health Office Work Area are: many employees have a high school education level, the South Sumatra Provincial Health Office can find a solution, including employees who arrive and go home not on time, a breakthrough and system is made that can improve employee performance. ABSTRAKTujuan penelitian ini adalah untuk menganalisis Kinerja ASN Diwilayah Kerja Dinas Kesehatan Provinsi Sumatera Selatan. Penelitian ini menggunakan pendekatan kualitatif dengan didukung data kuantitatif. Dalam penelitian ini peneliti bermaksud untuk memperoleh gambaran secara mendalam dan menyeluruh mengenai analisis kinerja ASN diwilayah kerja Dinas Kesehatan Provinsi Sumatera Selatan. Adapun pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Kesimpilan dari penelitian yaitu: 1). Kinerja ASN diwilayah kerja Dinas Kesehatan Provinsi Sumatera Selatan, dikategorikan baik. Kinerja Aparatur Sipil Negara (ASN) di wilayah kerja Dinas Kesehatan Provinsi Sumatera Selatan meliputi berbagai aspek seperti kemapuan dan keahlian, pengetahuan, rancangan kerja, kepribadian, motivasi kerja, kepemimpinan, gaya kepemimpinan, budaya organisasi, kepuasan kerja termasuk lingkungan kerja, serta laporan kinerja instansi pemerintah Dinas Kesehatan Provinsi Sumatera Selatan dapat memberikan gambaran yang lebih detail mengenai kinerja ASN di berbagai bidang tersebut, termasuk pencapaian, tantangan, dan upaya yang dilakukan untuk meningkatkan kinerja pegawai Dinas Kesehatan Provinsi Sumatera Selatan. 2). Permasalaham dalam Kinerja ASN Diwilayah Kerja Dinas Kesehatan Provinsi Sumatera Selatan adalah: banyak pegawai yang tingkat pendidikan SMU, dapat dicarikan solusinya oleh pihak Dinas Kesehatan Provinsi Sumatera Selatan, termasuk pegawai yang datang dan pulang tidak tepat waktu dibuatkan dilakukan sebuah terobosan dan sistem yang dapat meningkatkan kinerja pegawai.